Memantine in the Treatment of Executive Function Deficits in Adults With ADHD: A Pilot-Randomized Double-Blind Controlled Clinical Trial. (February 2017) - Biederman, Joseph; Fried, Ronna; Tarko, Laura; Surman, Craig; Spencer, Thomas; Pope, Amanda; Grossman, Rebecca; McDermott, Katie; Woodworth, K. Yvonne; Faraone, Stephen V.
Objective: To evaluate the efficacy and safety of memantine hydrochloride as an adjunct to stimulant pharmacotherapy for treating executive function deficits (EFDs) in adults with ADHD.Method: This was a 12-week, double-blind, placebo-controlled, randomized clinical trial of memantine added to open-label treatment with stimulant medication. Because of the small sample size, we considered a standardized mean difference (equivalent to effect size) of ≥0.5 and odds ratios ≥2 as indicators of trend improvements.Results: Twelve participants received memantine and 14 received a placebo. Trend improvements favoring memantine were observed on Behavior Rating Inventory of Executive Functions–Adult Inhibition and Self-Monitor subscales when compared with Placebo. No significant changes were noted on the Cambridge Neuropsychological Test Automated Battery.Conclusion: Among adults with ADHD and EFDs, adjunct treatment with memantine to osmotic release oral system-methylphenidate (OROS-MPH) was associated with improvements in selective areas of executive functioning, supporting the need for further research.